Human Brain Banking as a Convergence Platform of Neuroscience and Neuropsychiatric Research - Liu, Fan; Yin, Xiang-Sha; Cong, Cong; Wang, Yuanzhuo; Ma, Chao (Human Brain, 2022)
Neuropsychiatric disorders affect hundreds of millions of people and their families worldwide. Many studies have used human postmortem brain samples to decipher the molecular framework of these diseases. These studies uncovered brain-specific genetic and epigenetic patterns using high-throughput sequencing techniques. Therefore, determining the best way to collect human postmortem brain samples, analysing such a large amount of sequencing data, and interpreting these results is critical to advancing the field of neuropsychiatric sciences. By collecting postmortem/biopsied neural tissues and information about the diseases and life of donors, human brain banks support the observation and research of human brain sciences. Furthermore, the construction of large-scale brain banks has promoted the exploration of human brain morphology and function, development and ageing, as well as the mechanism of many neuropsychiatric diseases, which progressively reveal the normal mechanism of human brain activities and lead the direction of the prevention and treatment of neurological diseases. This article introduces the significance of human brain tissue bank construction and the current situation of the human brain tissue bank worldwide, as well as an overview of neurology or neuroscience advanced by using human brain samples.